PARTISIPASI PUBLIK DAN TRANSPARANSI DALAM REKRUTMEN PEGAWAI NEGERI SIPIL - Endah Setyowati (Jurnal Manajemen Kepegawaian, 2009)
Civil servant is an organizational resource that is very important in public organizations. Recruitment iseffective, efficien and fair will produce a professional civil sevant in the implementation of public participationis required in every implementation recruitment process. Aspects of transparency are not equality importantin the recruitment process, therefore the information in the recruitment process should be carried out in detailnot only the registration information, test requirements, but also the result of selection, including the valueof civil servant who pass the selection, so that the information in the web of each agency is information thewhole not cut to piecesKey words: participation, transparancy, recruitment